2013
DOI: 10.1093/qjmed/hct179
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis: incidence, presentation, causes and outcome in patients in a tertiary-care hospital in Karachi, Pakistan

Abstract: Anaphylaxis is a rare but life-threatening condition. Though cutaneous features are most common, their absence does not exclude the diagnosis. Drugs were the most common cause and epinephrine was not commonly used as first-line agent for its management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
10
14
0
2
Order By: Relevance
“…In line with most recently published studies of anaphylaxis in adults, food was the suspected trigger for the majority of anaphylaxis cases [6,8,14] and shellfish was the major food allergen triggering anaphylaxis [26]. In contrast, in a study conducted by our research team in a tertiary care pediatric ED, we found that peanut is the major food trigger in children [21].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In line with most recently published studies of anaphylaxis in adults, food was the suspected trigger for the majority of anaphylaxis cases [6,8,14] and shellfish was the major food allergen triggering anaphylaxis [26]. In contrast, in a study conducted by our research team in a tertiary care pediatric ED, we found that peanut is the major food trigger in children [21].…”
Section: Discussionsupporting
confidence: 86%
“…Epinephrine underuse has been reported in EDs from a variety of countries, including Pakistan [14], Puerto Rico [8], Italy [6], the United States [19] and Germany [15]. In the Italian study, only 2 patients among 18 with anaphylaxis received intramuscular epinephrine from an ambulance physician [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, studies conducted in a variety of countries also found poor adherence to guidelines [14,15]. Specifically, the underuse of epinephrine by paramedics was noted in a recent retrospective study concerning the EMS in Edmonton, Alberta, Canada [5].…”
Section: Discussionmentioning
confidence: 99%
“…Anafilaksi çeşitli tetikleyici ajanlarla temas sonrası ortaya çıkan, ciddi, fatal olabilen sistemik allerjik reaksiyondur (1)(2)(3)(4)(5). Tanısı öykü ve klinik şüphe ile konulmaktadır.…”
Section: Introductionunclassified